Design and Simulation of a Fuel Cell-based Hybrid Underwater Vehicle Propulsion System in Matlab/Simulink - Nguyen, Huy Chien; Hiep, Nguyen Ha (Engineering, Technology & Applied Science Research, 2024)
Remotely Operated Vehicles (ROVs) and Autonomous Underwater Vehicles (AUVs) have many applications in underwater missions. A recurring issue is managing the power source of the vehicle, especially air-independent propulsion sources, such as batteries, accumulators, and fuel cells, to increase diving depth, underwater endurance, and range. The current article proposes the use of both fuel cells and batteries simultaneously. The subject of the study is Pluto Plus ROVs, which are mine sweeping and counter-terrorism underwater vehicles. The considered system is simulated in Matlab/Simulink. The result was a block diagram that simulates a hybrid propulsion system for submersibles in general and serves as the basis for improving the propulsion system for Pluto Plus ROVs.